A within-country study of leadership perceptions and outcomes across native and immigrant employees: Questioning the universality of transformational leadership. (6th March 2017) - Holten, Ann-Louise; Bøllingtoft, Anne; Carneiro, Isabella Gomes; Borg, Vilhelm
Abstract: This study investigates the universality of transformational leadership with respect to employee perceptions and three outcomes: job satisfaction, self-rated health, and well-being. We do so among employees of different national and cultural backgrounds, yet within a shared national and sectorial setting. Our study has a repeated measures design based on survey data from 2, 947 employees (2, 836 natives Danes and 111 immigrants) in the Danish elder care sector. While we find no difference between native Danes and immigrants in their perception of transformational leadership, we find that transformational leadership is not a universal predictor of outcomes. Although transformational leadership predicts change in none of the outcomes for immigrants, it does predict change in job satisfaction and well-being for native Danes. Based on our findings, we suggest applying a combination of universalistic and contingency paradigms when leading composite employee groups.